Vice in the Nicomachean Ethics - Nielsen, K (Brill Academic Publishers, 2017)
This paper aims to articulate Aristotle’s general account of vice, an account that applies to all special vices, regardless of their spheres of action and emotion, and whether they are states of excess or deficiency. Vice is ignorance in the decision (ἡ ἐν τῇ προαιρέσει ἄγνοια): the paper explains what this means.